A new species of Anthopleura (Cnidaria: Anthozoa: Actiniaria) from the Mexican Pacific - Vassallo-Avalos, Aurora; González-Muñoz, Ricardo; Morrone, Juan J.; Acuña, Fabián H.; Durán-Fuentes, Jeferson A. [UNESP]; Stampar, Sérgio N. [UNESP]; Solís-Marín, Francisco A.; Rivas, Gerardo (Springer Nature, 2024)
Anthopleura is one of the most speciose genera within the family Actiniidae. This genus is particularly characterized by its members having both verrucae on the column and acrorhagi on the margin. In the region of the Baja California Peninsula, in the Mexican Pacific, six species of Anthopleura have been documented, which are relatively well defined by their morphological characteristics and coloration patterns. During recent visits to the intertidal zone of Cerritos, in Baja California Sur, we found individuals of Anthopleura displaying a variety of colorations that do not agree with known species for the region. We collected and examined specimens of four morphotypes of Anthopleura, analyzing them by integrating information about their external and internal anatomy, as well as their cnidome. Additionally, we obtained and analyzed genetic sequences from mitochondrial and nuclear markers through phylogenetic analyses. Our results reveal that the four morphotypes belong to a single, and undescribed species of Anthopleura. We provide a detailed description of the species Anthopleura variata sp. nov., which is characterized by a variety of coloration patterns, as well as having a circumscribed, palmate, and pedunculate marginal sphincter muscle, harboring zooxanthellae, and lacking directive mesenteries, among other characteristics. Anthopleura variata sp. nov. is the 49th species in the genus and the seventh species of Anthopleura documented for the Mexican Pacific.
Keywords: Actiniaria; Anthopleura; Baja California Peninsula; Mexican Pacific; Phylogenetic analysis; Taxonomy